(3GdcGaj aj Ydei GdYQhV hGdbhGais - (3YHjO Gddg Hf YHO GdcGai Hf YHO GdeLjO GdYHjOis; (3UOQGdOjf eMeO Hf Qcf GdOjf GdSGhjs ((3eMeO Hf GdMSjf s)
(3ChdgG (B:s
(3GdMeO ddg GdhGaQ HPGJg CeG HYO af GdbUjOI GdZQGA GdJi fXegG UOQ GdOfjG hGdOjf eMeO GdSGhi TQMJgG bHd gPG TQMkG hGajkG dcfg jSJOgi geekG YGdjg aQCjJ GdUhGH Cf CcJH TQMkG eMJhjkG Ydi GdebGUO s
(3BNQgG (B:s
(3gPG BNQ eG YfjJ HEedGFg ai TQM GdbUjOI GdYPQGA hfSCd Gddg JYGdi Cf jNaa YfG hCf jMTQfG ai ReQI ef QMeI HMb eMeO hBdg CLeYjf s
(3HMemO pdnedjc GdMb Pi GdWhd hGdYdi hTcQkG jG QH CaJJM eJaGFdkGs
(3HgG fXGe GdJYbjHIs
(3hgj TQM dbUjOI eMeO GdSGhi ai GdYQhV hGdJi ChdgG (B: s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdYQhV hGdbhGais